Communicating the Scientific Consensus on Climate Change: Diverse Audiences and Effects Over Time. Issue 7 (August 2022) - Goldberg, Matthew H.; Gustafson, Abel; van der Linden, Sander; Rosenthal, Seth A.; Leiserowitz, Anthony
Prior research has demonstrated that communicating the scientific consensus that human-caused climate change is happening is an effective way to increase public understanding and engagement with the issue. However, less is known about (1) how persuasive this message is to oppositional audiences, (2) how long message effects last over time, and (3) what factors predict whether such effects last. We address these questions in a two-wave longitudinal study and find that consensus messaging leads to updated consensus beliefs across Global Warming's Six Americas. Although consensus treatment effects decay over time, 40% of the original treatment effect remains 26 days later. Additionally, the treatment effect is most durable among people Doubtful or Dismissive of climate change. Our findings address an ongoing debate in the literature and support a Bayesian learning perspective, with little evidence of motivated reasoning.